Uma abordagem da matemática financeira no ensino médio para explicitar as metodologias do fundo de financiamento estudantil - FIES - Costa, Rivelino Duarte (2014)
This work aims to propose a methodology for learning present in the calculations of Financial Aid (FIES) tables, based on financial mathematics taught in high school. The work is divided into six parts: introduction, simple capitalization and composed, present value and future value, amortization of loans, the FIES tables and closing remarks. As a preamble, we have included the history of finance and the simple and compound capitalization. The proposal also suggests an understanding of the mathematical content of interconnected way, such as: simple interest with affine arithmetic progression and function, compound interest and exponential function with geometric progression, without forgetting the present and future value amount, representing the value right of capital in a given period. Thus, it is intended to achieve an understanding of the variations in the value of money during the time period and repayment of loans, facts that will bring the understanding of the type of system used in financing if Amortization System Constant Amortization System or French (PRICE).